Use of Internet and Social Media in Learning: Prof. Anwar Ul Haque - Haque, Prof. Anwar Ul (International Journal of Pathology, 2018)
Internet is one of the most useful and used modern devices. All over the world we see many people including children totally submerged in smart phones and laptops. Some are addicted; an addiction that could be as bad as drug addiction or even worse! I remember a cartoon showing a newborn whose umbilical cord was about to be cut; saying “Wait a minute first let me update my status”! Devices are not good or bad, it’s their use which makes the difference! We may use Facebook all day telling people what fashion we did, what we cooked or what we ate or where we went. These things add very little value for others and for us it may be shear waste of time and energy making us very tired at the end of the day that may have considerable toll on our health. Positive use of internet and social media on the other hand could be very rewarding; but we must not let it conquer us.